Perspektif Koneksionisme Terhadap Aktivitas Belajar di Era Teknologi Digital - Meutiawati, Ida (Desultanah: Journal Education and Social Science, 2024)
Connectionism learning has potential in learning activities in the digital digital era. This research aims to examine a new perspective on individual learning in a world full of information and connected to learning activities in the era of digital technology. The research method used is a literature study sourced from journal articles based on the theory of connectionism by using the keywords of learning connectionism in the digital era. Article search using the Google Scholar engine using Indonesian, the searched articles are limited from 2016 to 2024. The results of the study found several themes, namely the perspective of learning connectionism and learning activities in the era of digital technology. The research methods used in the analyzed articles were 6 articles in the qualitative method and 1 article in the development method. Furthermore, the articles analyzed are articles in 2016, 2021, 2022, 2023, 2024. Therefore, it can be concluded that connectionism has an influence in digital learning, such as the ability to improve the learning experience, as well as forming a relationship between stimuli and responses that are relevant in understanding and improving the quality of digital learning based on connectionism.